Tactile Collider: A new approach to the communication of fundamental science to visually impaired people. (1st February 2020) - Appleby, Rob; Edmonds, Chris; Watson, Robyn
Abstract : There is a large public interest in topics such as the Large Hadron Collider and the Higgs boson, primarily communicated to school children and the wider public using visual methods. As a result, visually impaired audiences of all ages often have difficulty accessing the scientific communication and may not be culturally involved in the scientific process. Tactile Collider aims to address this issue and has developed new methods of engaging visually impaired children and adults in science by the creation of the Tactile Collider model. This model has been developed with visual impairment (VI) experts and consultations, and implemented in a national touring event called Tactile Collider, visiting VI schools and centres around the country between 2017 and 2019. This paper describes the model and its development, and the use of the model to curate Tactile Collider events in 2017 and 2018. We present a quantitative and qualitative analysis of three 2018 events, showing the effectiveness of the approach and the engagement of the audience. The broader applicability is discussed.